2018
DOI: 10.1007/s00109-018-1688-8
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet consumption reduces hepatic folate transporter expression via nuclear respiratory factor-1

Abstract: Folate is an essential micronutrient for biological function. The liver, a primary organ for folate metabolism and storage, plays an important role in folate homeostasis. Proton-coupled folate transporter (PCFT) and reduced folate carrier (RFC) are the major folate transporters responsible for folate uptake at basolateral membrane of hepatocytes. Low serum folate levels are frequently associated with obesity. We investigated the mechanism that regulated folate status in a mouse model with diet-induced obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The liver, a primary organ for folate metabolism and storage, plays an important role in folate homeostasis . Yu et al found that an increased folate concentration would cause decreased expression of fatty acid synthesis genes including the peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer-binding protein α (C/EBPα), and fatty acid synthase (FAS) .…”
Section: Discussionmentioning
confidence: 99%
“…The liver, a primary organ for folate metabolism and storage, plays an important role in folate homeostasis . Yu et al found that an increased folate concentration would cause decreased expression of fatty acid synthesis genes including the peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer-binding protein α (C/EBPα), and fatty acid synthase (FAS) .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic consumption of high-fat diets (HFD) is a major contributor to the development of obesity and metabolic abnormalities. In our previous studies, we observed an increased body weight gain and metabolic abnormalities (hyperlipidemia, hyperglycemia) in mice fed a HFD for 5-12 weeks (11)(12)(13)(14)(15)(16). Recent studies demonstrated renal injury in dietinduced obese mice, a murine model of CKD (7,17).…”
Section: Introductionmentioning
confidence: 93%
“…Folate is an essential cofactor in metabolic pathways that influence DNA methylation patterns, DNA synthesis and cell proliferation ( Martino et al., 2018 ). A recent study shows that low levels of serum folate are frequently associated with obesity whereas chronic consumption of high-fat diets impairs folate transporter expression and leads to diminution of hepatic folate storage ( Sid, Siow, Shang, & Woo, 2018 ). Taken together, down-regulation of FOLH1 may contribute to elevation of glucose and lipid concentrations beyond reference ranges in the future mainly through affecting folate transporter expression or hepatic folate storage.…”
Section: Discussionmentioning
confidence: 99%